Development of high-temperature lead-free solder for semiconductor chip attachment / Ashraful Haque - Ashraful, Haque (2011)
Lead (Pb)-free electronic product is a catchphrase of consumer and different regulators worldwide which turns in to an obligatory for the electronic industries to remove Pb from semiconductor assembly for the reason that it is highly toxic, harmful for human health and environment. Alternative as well as drop-in-replacement of high-Pb solder used for Si die attachment in power device packaging is the bottleneck for the Pb-free electronic product. Operating temperature of such power devices is less than 250oC. In this study, two Bi-based, two Zn-Al-based alloys and one SAC-Cu epoxy solder were studied for Si die attachment on Cu lead-frame as a high-temperature Pb-free solder. Except SAC-Cu-epoxy solder, the other alloys were used in wire form to attach Ti/Ni/Ag metallized Si die on Cu lead-frame. Die attach was performed in automatic machine in a forming gas environment at temperature ranging from 370oC to 400oC. Interfacial reactions between lead-frame/solder and Si die/solder interfaces, bulk microstructure and die attach properties such as wetting, void, and die shear strength were investigated using optical, scanning electron microscope (SEM), energy dispersive x-ray (EDX) and electron probe microanalyzer (EPMA). Reliability tests such as autoclave (AC), temperature cycling (TC), high-temperature operating life (HTOL), high-temperature storage life (HTSL) were conducted for some selected solders. Die attach properties and reliability test results were compared with the standard Pb-5Sn soldered samples. Out of these Pb-free solders, void and wetting problem were encountered in Bi-based soldered samples to an extent which was not within acceptable limit. Moreover, for this solder, die displacement was observed during wire bonding process due to solder re-melt. Therefore, Bi-based alloys were not found suitable for high-temperature Pb-free solder. Among the Zn-Al-based alloys, Zn-Al-Ge solder was also associated with void problem which was not within acceptable limit. Average die shear strength of Zn-Al-Ge solder was found 22.3 MPa for die attach samples at 390oC which is close to the maximum operating temperature (400oC) of Si die. Due to void and small operating temperature window for die attachment, this solder is not suitable for Si die attachment. Zn-Al-Mg-Ga solder wetted well on Cu lead-frame, covered entire die area and flowed in all directions under the Si die. Cumulative void was found less than 10% for die attach temperature of 380oC and 390oC. Average die shear strength varies from 21.8 MPa to 29.4 MPa with the corresponding die attach temperature of 370oC and 400oC. Reliability test results of Zn-Al-Mg-Ga soldered samples were also found satisfactory. Die attach properties and reliability tests of SACCu epoxy soldered samples was also found within acceptable limit. However, creak was found in intermetallic compound layers at lead-frame/solder interface for Zn-Al- Mg-Ga soldered samples and at bulk for SAC-Cu epoxy soldered samples after 1000 thermal cycles and high-temperature operating life test which may affect on reliability during long term use.